Constructions of Apartheid in the International Reception of the Novels of J. M. Coetzee. - Barnett, Clive (Journal of Southern African Studies)
This paper discusses the international reception of the fiction of South African novelist and critic, J. M. Coetzee, in order to examine the institutional and rhetorical conventions which shaped the selection and circulation of particular forms of writing as exemplars of 'South African literature' from the 1970s through to the 1990s. The representation of Coetzee's novels in two reading-formations is critically addressed: in non-academic literary reviews; and in the emergent academic paradigm of post-colonial literary theory. It is argued that in both cases, South African literary writing has often been re-inscribed into new contexts according to abstract and moralised understandings of the nature of apartheid.